Using Activities as a Way of Proceduralization of Learners’ Language Knowledge - Gondova, Danica (Communications - Scientific letters of the University of Zilina, 2010)
The new education law [20, p. 5] emphasizes the importance of studying foreign languages in which learners should gain communicative competence and reach B2 level of the Common European Framework [2007] when they finish their secondary education. In order to achieve this objective, learners need to gain procedural knowledge of the target language. This objective is achievable if teachers activate learners and let them construct their own meanings of language in activities focused on gaining not only declarative knowledge, but also language habits and secondary language skills. Activities enable learners to work independently; teach them to think productively; and thus contribute to the development of their cognitive skills and autonomy. The multi-directional communication helps learners gain communicative competence and contributes to learners’ socialization.